An isomorphic multi-energy flow modeling for integrated power and thermal system considering nonlinear heat transfer constraint. (15th November 2020) - He, Ke-Lun; Chen, Qun; Ma, Huan; Zhao, Tian; Hao, Jun-Hong
Abstract: Development of unified electrical and thermal power flow model is critical for effective analysis of integrated power and thermal systems (IPTSs), where existing electric-analogy thermal circuit models of thermal systems are not analogous to that of power systems in physics, and heat transfer constraints of heat exchange facilities (HEFs) are usually simplified with inaccurate assumptions. Inspired by the irreversibility of transport phenomena, this work redefines the thermal resistance of HEFs and proposes a heat current model to comprehensively reflect heat transfer, migration and storage characteristics, which is in consistent with electrical power flow model and yields multi-energy flow model of IPTSs that can be solved using existing power system simulators. A multi-time scale hybrid simulation algorithm is further proposed and applied in simulating an urban IPTS. Results depict the developed method takes consideration of heat transfer characteristics of HEFs and secondary heating network accurately, which are ignored in traditional methods. Besides, introducing electric heat pumps as complementary heat sources to change the operation mode of combined heat and power plant from heat-led to power-led reduces 820.3 MWh wind curtailment by consuming 140.9 MWh electricity, where a 505.6 MWh heat stored in pipelines due to heat migration delay is fully exploited. Graphical abstract: Image 1 Highlights: Develop heat current model for heat transfer, migration and storage processes. Heat current model is consistent with power flow model of power system in physics. Proposed multi-energy flow model can be solved by existing power system simulator. Obtain temperature variations considering nonlinear heat transfer constraints. Applying auxiliary electrical heat pump effectively accommodates renewable energy.